More Than Skin Deep: Dermatologic Conditions in Athletes. (January 2023) - Pujalte, George G.A.; Costa, Lorena M.C.; Clapp, Adrianna D.; Presutti, R. John; Sluzevich, Jason C.
Context: Athletes are a unique group of patients whose activities, particularly in high-contact sports such as wrestling and football, place them at high risk of developing skin conditions. The correct diagnosis of sports dermatoses requires familiarity with their clinical characteristics. It is critical that primary care physicians recognize the most common skin disorders to provide prompt treatment and prevent transmission. Evidence Acquisition: The Mayo Clinic library obtained articles from 2012 onward related to dermatologic conditions in athletes. Study Design: Review article. Level of Evidence: Level 3. Results: Dermatologic diseases in athletes are often infectious and contagious due to close-contact sports environments. Sports-related dermatoses include bacterial infections, such as impetigo, ecthyma, folliculitis, abscesses, furuncles, carbuncles, erysipelas, and cellulitis; fungal infections, such as tinea and intertrigo; viral infections, such as herpes, verrucae, and molluscum contagiosum; and noninfectious conditions, such as acne, blisters, and contact dermatitis. Conclusion: This article aims to address the manifestations of the most common cutaneous diseases in athletes on the first primary care visit. It discusses the appropriate tests and most recent evidence-based treatments for each ailment. It also addresses return-to-play recommendations related to the guidelines and regulations of selected sports organizations in the United States. Strength of Recommendation Taxonomy (SORT): C.